A Micro Analysis of Demand-side Determinants of Schooling in Urban Pakistan (The Pakistan Development Review, 1993)
Investment in human capital is as important for growth as physical capital. The objective of this paper is to establish the importance of some factors, that affect the decision of a household to send their children who are of school going age, between 5-14 years, to school in urban areas. This paper is divided into five sections, Section 2 reviews the relevant schooling literature for Pakistan. Section 3 points some theoretical hypotheses describing the data and Section 4 presents the analysis, and finally Section 5 presents some conclusions.